Roles of parents in life satisfaction and educational hope among Chinese high school students - Han, Feng; Yuen, Celeste Yuet-Mui (Frontiers in Psychology, 2024)
This study employed self-determination theory and Bourdieu's sociocultural theory to examine the relationship between life satisfaction, educational hope, and parental support among Chinese high school students. A number of 3,810 high school students from eight schools in Jiangsu, China, completed a validated context-relevant questionnaire. Structural equation model analysis suggested that parental support significantly impacted students' life satisfaction and educational hope. Findings showed that parental intangible support in terms of providing information, advice, encouragement, praise, and care has a direct and significant impact on the life satisfaction of Chinese youth. The extent to which students attach importance to and put effort into achieving their educational aspirations, known as goal commitment, mediated the relationship between parental support and life satisfaction. Moreover, Chinese high school students' educational hope is shaped by their family. Parental support moderates goal commitment, which varies based on parental education background. In short, parents play a critical role in the growth and development of Chinese high school students.